Inﬂuence of varying concentrations of epoxy, rice husk,Al2O3, and Fe2O3on the properties of brake friction materials prepared using hand layup method - Irawan, Agustinus Purna; Fitriyana, Deni Fajar; Siregar, Januar Parlaungan; Cionita, Tezara; Anggarina, Paula Tjatoerwidya; Utama, Didi Widya; Rihayat, Teuku; Rusiyanto, Rusiyanto; Dimyati, Saeful; Aripin, Muhammad Bustanul; Ismail, Rifky; Bayuseno, Athanasius Priharyoto; et al. (MDPI, 2023)
Brake friction materials (BFMs) have a critical role in ensuring the safety as well as the reliability of automotive braking systems. However, traditional BFMs, typically made from asbestos, are associated with environmental and health concerns. Therefore, this results in a growing interest in developing alternative BFMs that are eco-friendly, sustainable, and cost-effective. This study investigates the effect of varying concentrations of epoxy, rice husk, alumina (Al2O3), and iron oxide (Fe2O3) on the mechanical and thermal properties of BFMs prepared using the hand layup method. In this study, the rice husk, Al2O3, and Fe2O3 were filtered through a 200-mesh sieve. Note that the BFMs were fabricated using different combinations and concentrations of the materials. Their mechanical properties, such as density, hardness, flexural strength, wear resistance, and thermal properties, were investigated. The results suggest that the concentrations of the ingredients significantly influence the mechanical and thermal properties of the BFMs. A specimen made from epoxy, rice husk, Al2O3, and Fe2O3 with concentrations of 50 wt.%, 20 wt.%, 15 wt.%, and 15 wt.%, respectively, produced the best properties for BFMs. On the other hand, the density, hardness, flexural strength, flexural modulus, and wear rate values of this specimen were 1.23 g/cm3, 81.2 Vickers (HV), 57.24 MPa, 4.08 GPa, and 8.665 × 10−7 mm2/kg. In addition, this specimen had better thermal properties than the other specimens. These findings provide valuable insights into developing eco-friendly and sustainable BFMs with suitable performance for automotive applications.